Eksplorasi konsep arsitektur dekonstruksi pada desain bangunan Planetarium Kota Makassar - Yahya, Amri; As, Zulkarnain; Febriansyah, Muhammad Chaidar (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Deconstructivist architecture is a branch of architecture that renews the form of modernism and tends to be minimalist, resulting in freer and more dynamic shapes with the aim of creating unique and characterful building designs. This research aims to design a planetarium in Makassar City using the principles and guidelines of deconstructivist architecture. The research process began with data collection through field surveys, followed by the formulation of the design concept. Primary data collection was carried out using descriptive methods, while secondary data was obtained from literature studies. The results show that the application of deconstructivist architecture concepts in the design of the Makassar City Planetarium is evident in design elements such as form, façade walls, aesthetic accents, and the use of vertical circulation within the building. This research is expected to contribute to the development of contemporary architecture and serve as a reference for designing buildings with similar concepts.